Modelling and fabrication of intake valve for Perodua Kancil engine - Nor Nashriq Azizi, Abd Shukor (2007)
This project tell about how to produce intake valve for Perodua Kancil engine. Objective for this project is to modeling and fabricating intake valve. The material that use is aluminium. Idea to fabricate this intake valve come after have many new model and shape in market. In that case, the information about how to produce the intake valve easy to get in internet. Three dimensional drawing for this intake valve is using Solidwork software, COSMOS Flow software to analysis about flow movement and produce by CNC Lathe Machine. In market, this intake valve is made by casting proses and finalize by turning (lathe) process. But, for this project, the intake valve is fully produce by CNC Lathe Process (turning process).